Dissecting the project anatomy: Understanding the cost of managing construction projects. Issue 2 (25th January 2023) - Haaskjold, Haavard; Andersen, Bjørn; Langlo, Jan Alexander
Abstract: The total cost of a construction project involves both the cost of production and the transaction costs associated with managing the project. However, we know surprisingly little about the magnitude of transaction costs in construction projects. The purpose of this paper is to provide more empirical data as we study what proportion of the total cost in construction projects is spent on managing the project. We use the analogy of human anatomy as we investigate the size of a project's head (managing the project) compared to the size of its body (producing deliverables). Using a dataset from 134 construction projects in Norway, we find that the project head consists of more than 18% of the total project cost on average. We also investigate how the size of the project head varies depending on a project's complexity, size, duration and burn rate.